Arctica sp. - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
? Arctica sp. Fig. 14. 1925 Astarte spec.; Hägg 1925: 45, pl. 3: 9. 2016 Astartiidae? sp. 1; Hryniewicz et al. 2016: table 2. Material. — One specimen (NRM-PZ Mo 149143), shell, from the upper Paleocene of Fossildalen, Spitsbergen, Svalbard. Measurements. —NRM-PZ Mo 149143: L, 26.9 mm; H, 22.5 mm; W, 12.5 mm. Description. —Shell medium-sized, oval with prosogyrate, weakly anteriorly incurved umbones. Anterodorsal margin concave, with incised lunular area, anterior margin rounded, continuous with rounded ventral margin. Posterior margin rounded, passing into straight, dorsally inclined posterodorsal margin. Outer surface sculptured with many very fine growth lines (8 per 1 mm). Details of inner shell surface unknown. Remarks. —After closer examination of the specimen illustrated by Hägg (1925), we conclude it is most likely a species of Arctica sp. based on the external shell shape, position and character of the beak, straight and dorsally inclined posterodorsal shell margin, and numerous very fine commarginal growth lines. The latter character could be related to very slow growth (Morton 2011), known from the extant long-living species Arctica islandica (Linnaeus, 1767). Arctica ovata (Meek and Hayden, 1858) from the Paleocene Cannonball Formation of South and North Dakota Cvancara 1966) and Danian (lower Paleocene) Prince Creek Formation in Alaska (Marincovich 1993), both USA, is similar to? Arctica sp. in general shell shape. However, due to the lack of data on the dentition of the Svalbard material, we are unable to compare the two species in more detail. The same applies to Arctica sp. 1 from the lower Danian Paleocene) Agatdal Formation in Nuussuaq (Petersen and Vedelsby 2000), Greenland. Published as part of Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M. & Kaim, Andrzej, 2019, A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard, pp. 101-141 in Acta ...